Physical–Mechanical Properties and Mineral Deposition of a Pit-and-Fissure Sealant Containing Niobium–Fluoride Nanoparticles—An In Vitro Study - Obeid, Alyssa Teixeira; Nascimento, Tatiana Rita de Lima; Ramos, Carlos Alberto Spironelli; Mondelli, Rafael Francisco Lia; Rastelli, Alessandra Nara de Souza [UNESP]; Alhotan, Abdulaziz; Velo, Marilia Mattar de Amoêdo Campos [UNESP]; Bombonatti, Juliana Fraga Soares (MDPI, 2024)
This study investigated the combined effects of adding niobium–fluoride (NbF5) nanoparticles to a pit-and-fissure sealant. One resin sealant was reinforced with varying amounts of nanoparticles (0.3, 0.6, and 0.9 wt%). The surface hardness (SH), energy-dispersive X-ray spectroscopy (EDX), surface roughness (Ra), color change (ΔE), and mineral deposition were assessed. Bovine enamel blocks were subjected to demineralization and pH-cycling for SH. The elemental composition and Ca/P ratio were evaluated using EDX, while the mineral deposition was measured using Fourier transform infrared spectroscopy (FTIR). Data were analyzed using ANOVA and Tukey’s test for the SH and EDX, ΔE, and Kruskal–Wallis for the Ra. The NbF5 modification increased the SH, with the 0.9 wt% sealant exhibiting higher SH values, and the 0.3 wt% one exhibiting significant differences compared to the control and the 0.9 wt% (p = 0.00) samples, even after pH-cycling. For the EDX analysis, the 0.3 and 0.6 wt% samples exhibited higher Ca/P ratios, with the 0.3% one showing evidence of P-O crystal formation. There was no significant difference in the Ra (p = 0.458), and the 0.6 and 0.9 wt% ones showed lower ΔE values compared to the control. The 0.3 wt% NbF5 demonstrated improved overall properties, making these results particularly promising for preventing tooth decay, reducing demineralization through increased ions release and promoting remineralization in posterior teeth.
Keywords: fluoride; nanoparticles; niobium; pit-and-fissure sealants